A STUDY ON SPEAKING ANXIETY IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM OF THE THIRD SEMESTER STUDENTS AT ENGLISH DEPARTMENT OF UNIVERSITY OF ISLAM MALANG - Vara Arsyilia Fitriani (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Spoken language is the act of conveying information or expressing thoughts and feelings in English. Language anxiety is a very common issue that affects student speaking output. Language anxiety, a dynamic psychological construct, is known to be an effective component in language learning. Anxiety is a feeling of fear, tension, and apprehension about what’s to come. The purpose of this study was to determine the level of students' speaking anxiety and to find out the factors that influence students’ anxiety in the English classroom. The research methodology is a descriptive quantitative and qualitative study. Research instruments are the questionnaire of foreign language class anxiety scale (FLCAS) adapted from Elaine Kolker Horwitz, Michael Horwitz, & Joann Cope (1986) to determine the level of students' speaking anxiety and using interview adapted from Price (1991) to find out the factor of speaking anxiety. The results of this study show that the main anxiety level experienced by students occurs in "middle anxiety" with 43% in range (87-107). Low self-esteem and students’ beliefs, speaking in front of the class, fear of making mistake and lecture’s performance are the factors underlying speaking anxiety in the English class.Keywords: Speaking Anxiety, Level Speaking anxiety, Factor speaking anxiety